Re‐annotation, improved large‐scale assembly and establishment of a catalogue of noncoding loci for the genome of the model brown alga Ectocarpus. Issue 1 (21st November 2016) - Cormier, Alexandre; Avia, Komlan; Sterck, Lieven; Derrien, Thomas; Wucher, Valentin; Andres, Gwendoline; Monsoor, Misharl; Godfroy, Olivier; Lipinska, Agnieszka; Perrineau, Marie‐Mathilde; Van De Peer, Yves; Hitte, Christophe; et al.
Summary: The genome of the filamentous brown alga Ectocarpus was the first to be completely sequenced from within the brown algal group and has served as a key reference genome both for this lineage and for the stramenopiles. We present a complete structural and functional reannotation of the Ectocarpus genome. The large‐scale assembly of the Ectocarpus genome was significantly improved and genome‐wide gene re‐annotation using extensive RNA‐seq data improved the structure of 11 108 existing protein‐coding genes and added 2030 new loci. A genome‐wide analysis of splicing isoforms identified an average of 1.6 transcripts per locus. A large number of previously undescribed noncoding genes were identified and annotated, including 717 loci that produce long noncoding RNAs. Conservation of lncRNAs between Ectocarpus and another brown alga, the kelp Saccharina japonica, suggests that at least a proportion of these loci serve a function. Finally, a large collection of single nucleotide polymorphism‐based markers was developed for genetic analyses. These resources are available through an updated and improved genome database. This study significantly improves the utility of the Ectocarpus genome as a high‐quality reference for the study of many important aspects of brown algal biology and as a reference for genomic analyses across the stramenopiles.